Workplace Bullying: A Process Model of Unbalanced Psychological Contract Fulfillments - Nawakitphaitoon, Kritkorn; Hoch, Julia (Human Resource and Organization Development Journal, 2019)
This conceptual paper presents the process whereby supervisors engage in bullying behavior against their subordinates at work. The model draws on Emerson’s (1962) power dependence theory to link psychological contract fulfillment with the bullying literature. Specifically, a conceptual model is developed to portray the process by which supervisors who perceive an unbalanced psychological contract fulfillment (under- or over-fulfilled) might commit one of two different types of workplace bullying (person- or work- related bulling) toward subordinates through the process intended to restore or maintain their sense of power. In addition, self-control and organizational culture are proposed to be the moderators that can affect the relationship between under- and over- fulfilled psychological contracts and bullying perpetration. The model thus contributes to the literature by highlighting the process and interactions of how bullying behavior occurs in the workplace.